The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1128/aac.01134-18
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Full-Length Lanosterol 14α-Demethylases of Prominent Fungal Pathogens Candida albicans and Candida glabrata Provide Tools for Antifungal Discovery

Abstract: Targeting lanosterol 14α-demethylase (LDM) with azole drugs provides prophylaxis and treatments for superficial and disseminated fungal infections, but cure rates are not optimal for immunocompromised patients and individuals with comorbidities. The efficacy of azole drugs has also been reduced due to the emergence of drug-resistant fungal pathogens. We have addressed the need to improve the potency, spectrum, and specificity for azoles by expressing in functional, recombinant, hexahistidine-tagged, full-lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 37 publications
1
78
0
Order By: Relevance
“…The presence of PCZ instead of VT-1161 in the SEC allows N-truncCaLDM6ϫHis A61-Q66, F238-F235, and Y506-M509 to adopt a conformation significantly closer to that found in the full-length ScLDM6ϫHis structures. The PCZ ligand has a conformation essentially identical to its congener ITC in crystal structures obtained with fulllength ScLDM6ϫHis and full-length CaLDM6ϫHis (36). Like ScLDM6ϫHis in complex with ITC, the PCZ complex has the piperazine ring in a chair conformation ( Fig.…”
Section: Figmentioning
confidence: 92%
See 2 more Smart Citations
“…The presence of PCZ instead of VT-1161 in the SEC allows N-truncCaLDM6ϫHis A61-Q66, F238-F235, and Y506-M509 to adopt a conformation significantly closer to that found in the full-length ScLDM6ϫHis structures. The PCZ ligand has a conformation essentially identical to its congener ITC in crystal structures obtained with fulllength ScLDM6ϫHis and full-length CaLDM6ϫHis (36). Like ScLDM6ϫHis in complex with ITC, the PCZ complex has the piperazine ring in a chair conformation ( Fig.…”
Section: Figmentioning
confidence: 92%
“…The crystal structures include the complete protein primary sequence from serine 6 (S6) for the ScLDM-VT-1161 complex and from valine 8 (V8) to the first histidine in the C-terminal hexahistidine tag for the ScLDM-PCZ complex. (36). The crystal structure of ScLDM6ϫHis in complex with PCZ shows a 2.1-Å 6th axial (distal) coordination with the heme iron via N-3 of the triazole ring, which projects toward helix I (Fig.…”
Section: Fig 1 Susceptibilities Of Yeast Constructs and Clinical Isolmentioning
confidence: 98%
See 1 more Smart Citation
“…This approach has enabled robust assessment of the response of LDMs from two major fungal pathogens of humans to both established and novel antifungals and expression of functional fungal LDMs for structural analysis. For example, we have used X-ray crystal structures for full-length S. cerevisiae (2), C. glabrata, and C. albicans LDMs (see the companion paper [33]) to define a deep LBP comprised of an active site, SEC, and putative product exit channel relevant to a wide range of fungal pathogens. In silico screens that identify and rank hits that dock with the crystal structures and derived homology models can now be combined with phenotypic screens to identify agents that target the fungal enzyme in biological contexts.…”
Section: Ergosterol Content Is Affected By Ldm and Ncp1 Expressionmentioning
confidence: 99%
“…As discussed in the previous section, azole drugs bind with lanosterol 14a-demethylase and inhibit ergosterol biosynthesis 24 Here, we performed in silico molecular docking studies of 5n with CaCYP51 to validate our sterol quantitation analysis. Interestingly, the study revealed that compound 5n showed polar interaction with heme atom in the binding site.…”
Section: Docking Studiesmentioning
confidence: 99%